CGRP restrains CD4+ T cell responses and allergic sensitization - Li, Xiaoshi; Zhang, Ying; Chen, Wenlong; Meng, Qingren; Huang, Ai; Pan, Jiayi; Chen, Duan; Xiao, Yue; Wei, Jialin; Sun, Heng; Liu, Quan (Frontiers in Immunology, 2025)
BackgroundCalcitonin gene-related peptide (CGRP), a neuropeptide released by sensory neurons, plays an emerging role in immune regulation, yet its function in adaptive immunity remains poorly understood. Here, we identify the CGRP–RAMP1 pathway as a key intrinsic regulator of CD4+ T cell responses during allergic sensitization.MethodsHouse dust mite (HDM) was used to induce allergic sensitization in mice. CGRP+ sensory nerve fiber distribution in mediastinal lymph nodes (medLNs) was analyzed with whole-mount imaging. RAMP1 expression on immune cells was assessed with a RAMP1-mCherry reporter by flow cytometry. TCR-seq, parabiosis, and adoptive transfer were employed to assess the biological roles of RAMP1 expression in CD4+ T cells. In vitro, CD4+ T cells were stimulated, differentiated, and analyzed by flow cytometry, ATAC-seq, and RNA-seq to evaluate the impact of CGRP. CD4+ T cell-specific RAMP1 knockout mice and CGRP treatment were used to evaluate immune cell infiltration and Tfh responses in allergic sensitization. Additionally, Calca−/−, Ramp1−/−, and CD4+ T cell-specific RAMP1 knockout mice were used from immunological studies in the HDM-induced allergic asthma model. CGRP was intraperitoneally injected to evaluate its preventive effect on asthma.ResultsCGRP+ fibers densely innervate medLNs. In CD4+ T cells, RAMP1 is preferentially expressed on naïve ones. While RAMP1 does not affect thymocyte development, TCR diversity, or tissue residency, CGRP–RAMP1 signaling suppresses CD4+ T cell activation and differentiation. CGRP reshapes chromatin accessibility and transcriptional programs to suppress a responsive state and repress Tfh-associated gene expression of CD4+ T cells. Following allergen sensitization, the density of CGRP+ fibers in the medLNs is reduced. CD4+ T cell-specific RAMP1 deficiency promotes Tfh cell accumulation and B cell activation in the medLNs, exacerbating allergic sensitization. Conversely, exogenous CGRP treatment mitigates allergic sensitization in a RAMP1-dependent manner. Finally, CGRP treatment during the sensitization phase effectively alleviates allergic asthma.ConclusionsThese findings suggest a neuroimmune axis in which CGRP–RAMP1 pathway restrains allergic sensitization by directly modulating the immunobiology of CD4+ T cells.